2023
DOI: 10.1001/jamanetworkopen.2023.1153
|View full text |Cite
|
Sign up to set email alerts
|

Rural-Urban Variation in the Association of Adolescent Violence and Handgun Carrying in the United States, 2002-2019

Abstract: ImportanceAdolescent handgun carrying is associated with increased risk of firearm-related violence. Most evidence on adolescent handgun carrying is from urban areas, but these findings may not generalize to rural areas.ObjectiveTo examine differences in associations of adolescent interpersonal violence with handgun carrying across the rural-urban continuum.Design, Setting, and ParticipantsThis cross-sectional study used nationally representative data from the US National Survey on Drug Use and Health among ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Second, our findings extended the existing literature showing that alcohol use may precede subsequent handgun carrying. Third, we expanded on the existing literature by exploring these associations longitudinally using data from the last two decades, during which youth handgun carrying and firearm‐related harm have increased in rural areas 37,38 . Overall, we found that any alcohol use was associated with higher odds of subsequent handgun carrying and the odds were greater with heavy drinking.…”
Section: Discussionmentioning
confidence: 86%
“…Second, our findings extended the existing literature showing that alcohol use may precede subsequent handgun carrying. Third, we expanded on the existing literature by exploring these associations longitudinally using data from the last two decades, during which youth handgun carrying and firearm‐related harm have increased in rural areas 37,38 . Overall, we found that any alcohol use was associated with higher odds of subsequent handgun carrying and the odds were greater with heavy drinking.…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, rural adolescents may have an increased propensity for increased weapon carrying due to victimization (e.g., attacked, sexually assaulted; Kingery et al, 1996). For instance, the prevalence rates of gun carrying after experiencing violence in a fight was higher in urban than rural areas (Schleimer et al, 2023). However, the prevalence difference of gun carrying between individuals who had a serious fight and those who did not was 12.3% in rural areas and only 5.2% in urban areas (Schleimer et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the prevalence rates of gun carrying after experiencing violence in a fight was higher in urban than rural areas (Schleimer et al, 2023). However, the prevalence difference of gun carrying between individuals who had a serious fight and those who did not was 12.3% in rural areas and only 5.2% in urban areas (Schleimer et al, 2023). Additionally, rural individuals who were involved in a group fight versus those who were not had a prevalence difference of 21.8% while urban areas only had a difference of 7.5% (Schleimer et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations